Enhacing security in banking transactions using artificial intelligence - A. A. Nedbaev; S. P. Spiridonov (Путеводитель предпринимателя)
The paper explores modern approaches to securing banking transactions through artificial intelligence (AI) technologies. Machine learning methods for preventing fraudulent activities against users are analyzed, along with the advantages and disadvantages of implementing AI in the banking sector.